Alzheimer's 100th anniversary of death and his contribution to a better understanding of Senile dementia - Eliasz Engelhardt; Marleide da Mota Gomes (Arquivos de Neuro-Psiquiatria)
Initially the trajectory of the historical forerunners and conceptions of senile dementia are briefly presented, being highlighted the name of Alois Alzheimer who provided clinical and neuropathological indicators to differentiate a group of patients with Senile dementia. Alzheimer's examination of Auguste D’s case, studied by him with Bielschowsky’s silver impregnation technique, permitted to identify a pathological marker, the intraneuronal neurofibrillary tangles, characterizing a new disease later named after him by Kraepelin – Alzheimer’s disease. Over the time this disorder became one of the most important degenerative dementing disease, reaching nowadays a status that may be considered as epidemic.